The Neurologic Diagnosis A Practical Bedside Approach - Alpert, Jack N.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
The Neurologic Diagnosis: A Practical Bedside Approach is an introductory text that simplifies the often unwieldy method of making a neurologic diagnosis. Medical students are often intimidated by a deluge of data, extensive differential diagnoses, and have no organizational structure to follow. Diagnostic techniques of general medicine are not applicable. Neurology is a unique specialty since it requires the intermediary step of an anatomic diagnosis prior to proffering a differential diagnosis. Yet the required knowledge of neuroanatomy need not be profound for the student who will specialize in any field other than neurology and neurosurgery. This text is directed to medical students and residents who will all be regularly faced with numerous patients who have neurologic symptomatology. Typical one-month neurology rotations out of four years of medical school is clearly inadequate training to make a cogent neurologic diagnosis, especially since subsequent instruction is commonly provided by upper level residents who have the same background and numerous misconceptions. This is not a comprehensive text. The emphasis in this concise and practical title is on establishing a neuroanatomic diagnosis before formulating a differential diagnosis. In addition, treatment is seldom discussed since it is likely to change radically over time. Focused and succinct, The Neurologic Diagnosis: A Practical Bedside Approach is an invaluable resource for medical students and residents interested in the practice of neurological diagnosis.
Forward -- Preface -- Introduction -- The Ten Neuroanatomic Diagnoses -- The Neurologic History Holds the Diagnostic Keys -- Neurologic Examination -- Evaluation of the Poorly Responsive Patient -- The Six Major Anatomic Decussations with Clinical Correlation -- Cerebrovascular Anatomy with Clinical Correlation -- Autonomic Nervous System Anatomy with Clinical Correlation -- Neuromuscular Diseases: Neuroanatomic and Differential Diagnoses -- Common Symptoms in the Neurology Clinic -- Diagnostic Dilemmas -- Neurologic Terminology -- Index to Diseases.
Keywords: Medicine; Neurology; Medicine & Public Health; Neurology